2004
DOI: 10.1111/j.1523-1755.2004.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal-dominant Alport syndrome: Natural history of a disease due to COL4A3 or COL4A4 gene

Abstract: This paper demonstrated that patients affected by autosomal-dominant Alport syndrome have a high clinical variability. Moreover, a reduced penetrance of about 90% (3 of 25) may be considered for the assessment of recurrence risk during genetic counseling of these families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 19 publications
3
85
0
3
Order By: Relevance
“…Five mutations detected in patients with ADAS in this study were previously reported as causative mutations for ARAS (11,18). Interestingly, the heterozygous carrier parents of these mutations in those reports were asymptomatic or only presented with microhematuria.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Five mutations detected in patients with ADAS in this study were previously reported as causative mutations for ARAS (11,18). Interestingly, the heterozygous carrier parents of these mutations in those reports were asymptomatic or only presented with microhematuria.…”
Section: Discussionmentioning
confidence: 73%
“…A recent study using next generation sequencing (NGS) analysis revealed high proportions of mutations in COL4A3 and COL4A4 and a higher incidence of ADAS than previously reported (6). However, studies of ADAS are limited, and the clinical phenotype and genetic and pathologic backgrounds remain unclear (7)(8)(9)(10)(11)(12). In this study, we provide the first clarification of the genetic, clinical, and pathologic backgrounds of ADAS in a relatively large number of patients.…”
Section: Introductionmentioning
confidence: 83%
“…First, the possibility that TBMN may not be benign in terms of ultimate prognosis has been considered before (13,14,18,30,25), and ESRD similar to that seen in AS was reported in adults with heterozygote COL4A3/A4 mutations (occasionally also referred to as "autosomal dominant Alport syndrome") (15,34 -37). It should be noted that it was suggested that the molecular type of COL4A3/A4 mutations and additional modifier genes are likely to influence the severity of the renal phenotype eventually (35,36,37). Second, hypertension in adults with TBMN was reported previously and is likely to worsen the general prognosis of affected patients (13,25).…”
Section: Discussionmentioning
confidence: 99%
“…To date, 71 COL4A3 variants that include mis-sense, nonsense, deletion, insertion, and splice-site changes have been determined, 52 of which are related with autosomal-recessive or autosomaldominant AS. The other COL4A3 mutations have been found to be related with hematuria, focal segmental glomerulosclerosis, microhematuria, and proteinuria, and one mutation has been found to be related with chronic obstructive pulmonary disease Ding et al, 1995;Knebelmann et al, 1995;Van Der Loop et al, 2000;Heidet et al, 2001;Badenas et al, 2002;Longo et al, 2002;Tazon et al, 2003;Pescucci et al, 2004;Wang et al, 2004;Nagel et al, 2005;Longo et al, 2006;Hou et al, 2007;Slajpah et al, 2007;Voskarides et al, 2007;Hou et al, 2008;Kim et al, 2008, Hoefele et al, 2010Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%